2005
DOI: 10.1001/archneur.62.6.917
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Substantia Nigra in Parkinson Disease, Progressive Supranuclear Palsy, and Frontotemporal Dementia With Parkinsonism

Abstract: Background: Parkinson disease (PD) is characterized by loss of dopaminergic neurons in the substantia nigra. Genes contributing to rare mendelian forms of PD have been identified, but the genes involved in the more common idiopathic PD are not well understood.Objectives: To identify genes important to PD pathogenesis using microarrays and to investigate their potential to aid in diagnosing parkinsonism.Design: Microarray expression analysis of postmortem substantia nigra tissue.Patients: Substantia nigra sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 23 publications
6
121
0
3
Order By: Relevance
“…Here, we describe gene regulatory relationships between SNCA and two other pathways considered to be of relevance in PD, dopamine synthesis and parkin metabolism. Supplemental File 6 provides a comparison of our gene list with findings from other microarray studies in SN of sporadic PD (see [22,23,43,75]). …”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe gene regulatory relationships between SNCA and two other pathways considered to be of relevance in PD, dopamine synthesis and parkin metabolism. Supplemental File 6 provides a comparison of our gene list with findings from other microarray studies in SN of sporadic PD (see [22,23,43,75]). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hsp70 has been shown to enhance α-synuclein refolding or degradation, thereby decreasing α-synuclein fibrillization and toxicity (Klucken et al 2004;Luk et al 2008). There is an increase in the expression of HSPA1A and HSPA1B in the substantia nigra of patients with Parkinson's disease, progressive supranuclear palsy, and frontotemporal dementia with parkinsonism (Hauser et al 2005). In their report, Hauser and colleagues further suggested that Hsp70 induction was a "common response to mitigate the toxic effects of misfolded protein."…”
Section: Heat Shock Proteins In Neurodegenerative Disorders and Agingmentioning
confidence: 99%
“…In brief, total RNA was used for cDNA synthesis employing the Super-Script double-stranded cDNA synthesis kit (Superscript Choice System, Life Technologies, Gaithersburg, MD) with the T7-(dT) 24 primer. In vitro transcription was performed using the Enzo-IVT kit (Enzo BioArray High Yield RNA Transcript Labelling Kit, Enzo Diagnostics, Farmingdale, New York, USA).…”
Section: Preparation Of Target Crna For Microarraysmentioning
confidence: 99%